Mobilisasi Tabungan Antara Keuangan Formal Dan Informal Dalam Sistem Keuangan Syariah - Misbahul Khoir (JES (Jurnal Ekonomi Syariah), 2017)
Islam as a rule of life (nizam al-hayat) governs all sides of human life, including in terms of economic transactions, in doing saving activities too. So it also affects the institutions that receive savings funds. The definition of the Islamic financial system itself is a financial system that channels between parties who need funds and parties who have excess funds through financial products and services in accordance with the principles of sharia. The sharia principle is a principle based on the teachings of the Qur'an and Sunnah. In the Indonesian context, sharia principle is the principle of Islamic law in banking and finance activities based on fatwa issued by institutions that have authority in the establishment of fatwa in the field of sharia. From the background, the above description contains two important points. First, how is way of saving and investing from an Islamic point of view. Second, what is definition of Islamic Financial System. Both of these are first step in describing as problem in the scope of savings mobilization between formal and informal finance in the Islamic financial system. Islam forbids allowing idle assets, and encourages every wealth that we have to invest in the real sector. Saving is not a disbelief of the existence of sustenance from Allah SWT. Saving is a good management process of the provision of Allah SWT as a reflection of the attitude of our trust for sustenance given by Allah SWT. So it can be concluded, in the teachings of Islam, the saving is effort on the alert and as part of the household financial management process. By saving we have a time-forward perspective because it not only looks at short-term expenditures, but has made predictions of preparation for the future. Saving is part of self-control. By saving, it means that we are not carried by lust to meet the fulfillment of present or short-term satisfaction, but to control the fulfillment of our desire to be able to meet the needs of the future which is much more important. Saving is not a barrier for a person to give alms or zakah. People whose faith is strong and accustomed to saving then he will be able to expel zakah well and give alms more. People who are used to saving means having good financial planning. If so, the funds that he has will be more optimal, so will be able to pay zakah well and give alms more because the funds are well managed. Keywords: Saving Mobility, Formal and Informal Finance, Sharia Financial System